APPLICATION OF THE PRINCIPLE OF EQUALITY BEFORE THE LAW IN THE CASE AMMAR ZONI'S NARCOTICS CRIME - Elsa Efritha Wijaya; Diding Rahmat; Sudarto (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
This study aims to analyze the regulation and implementation of the principle of equality before the law within the Indonesian legal system, particularly in the enforcement of narcotics crime involving Ammar Zoni based on the Decision of the Central Jakarta District Court Number 632/Pid.Sus/2025/PN.Jkt.Pst. The principle of equality before the law is a fundamental concept in a rule of law state, which affirms that every individual has equal standing before the law without any form of discriminatory treatment. This research uses normative legal research methods with a statutory approach and a case approach. The data used in this study are secondary data consisting of primary, secondary, and tertiary legal materials obtained through library research. The data were analyzed qualitatively by interpreting and systematically examining relevant legal materials. The results of the study show that normatively the principle of equality before the law has been clearly regulated in the Indonesian legal system, particularly in Article 27 paragraph (1) and Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia as well as various statutory regulations governing the criminal justice system, including Law Number 35 of 2009 concerning Narcotics. In its application to the case involving Ammar Zoni, the legal process was carried out through the general criminal justice mechanism without any special treatment toward the defendant as a public figure. The panel of judges based their decision on valid evidence presented in court and the applicable legal provisions. Thus, procedurally, the principle of equality before the law in this case has been implemented through an objective judicial process based on the facts revealed during the trial.